Changes in health status of North Korean children and emerging health challenges of North Korean refugee children - Seong-Woo Choi (The Korean Pediatric Society, 2021)
The food shortage in North Korea is a serious situation that has spanned the mid-1990s to today. North Korean refugee children, even those born in North Korea, China, or South Korea, had poor nutritional status at birth; thus, their growth and nutritional status should be continuously monitored. This review focused on the health status of North Korean children and the nutritional status of North Korean refugee children upon settling in South Korea. Immediately after entering South Korea, North Korean refugee children were shorter and lighter than South Korean children and had a serious nutritional status. Over time, their nutrition status improved, but they remained shorter and lighter than South Korean children. A new obesity problem was also observed. Therefore, it is necessary to continuously monitor their growth and nutritional status.